Molecular interplay of autophagy and endocytosis in human health and diseases. (15th April 2019) - Mahapatra, Kewal K.; Panigrahi, Debasna P.; Praharaj, Prakash P.; Bhol, Chandra S.; Patra, Srimanta; Mishra, Soumya R.; Behera, Bishnu P.; Bhutia, Sujit K.
ABSTRACT: Autophagy, an evolutionarily conserved process for maintaining the physio‐metabolic equilibrium of cells, shares many common effector proteins with endocytosis. For example, tethering proteins involved in fusion like Ras‐like GTPases (Rabs), soluble N‐ethylmaleimide sensitive factor attachment protein receptors (SNAREs), lysosomal‐associated membrane protein (LAMP), and endosomal sorting complex required for transport (ESCRT) have a dual role in endocytosis and autophagy, and the trafficking routes of these processes converge at lysosomes. These common effectors indicate an association between budding and fusion of membrane‐bound vesicles that may have a substantial role in autophagic lysosome reformation, by sensing cellular stress levels. Therefore, autophagy–endocytosis crosstalk may be significant and implicates a novel endocytic regulatory pathway of autophagy. Moreover, endocytosis has a pivotal role in the intake of signalling molecules, which in turn activates cascades that can result in pathophysiological conditions. This review discusses the basic mechanisms of this crosstalk and its implications in order to identify potential novel therapeutic targets for various human diseases.